THE ROLE OF TELEGRAM DIGITAL MEDIA FOR CLASS C STUDENTS OF UNIVERSITY DARUSSALAM GONTOR - Saniah fajrin; Hasna' Titania Nabila; Siti Khoirun Nabilatuz Zahro'; Diah Rukmini (Universitas Mercu Buana, 2026)
Telegram is a social media to communicate for all female students of University Darussalam Gontor Class C. With the limited electronic and communication tools used by female students, they use a social application called telegram to communicate with each other. In this study, researchers explained about features that are accessed by all female students and can also be accessed by other users. The Services provided by telegram social media, to the benefits they get through telegram with its many bot features and various existing channels. This type of research is qualitative descriptive research, researchers use qualitative research methods because they want to explore a fact, symptom or event of the influence of the use of telegram chat media for students of Darussalam Gontor University Class C, as female students only use telegram chat media to connect with fellow students, even with lecturers of Darussalam Gontor University though. Researchers obtain results through observation and documentation validated by triangulation of sources, methods, and time. The results of the research needed by researchers are how important this digital media is for students of Universitas Darussalam Gontor Class C with the many features of this telegram and some of the benefits of the role of digital media for female students.